Technology Integration in Educational Management: Its Impact on Community Participation - Kurniawan, David Rindu; Purnama, Yulian; Siminto; Riady, Yasir; Az Zaakiyyah, Hizbul Khootimah (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Education has undergone a paradigm shift from conventional approaches towards the integration of technology as an integral part of the learning process. This transformation aims to enhance the effectiveness and efficiency of learning while preparing students to face increasingly complex global challenges. The objective of this research is to analyze the integration of technology in educational management and its impact on community participation. This study employs a qualitative literature review method with a focus on data collection from Google Scholar for the period 2012-2023. The study's findings indicate that the integration of technology in educational management has brought about fundamental changes in the field of education, not only in administrative aspects but also in community involvement. This transformation has created an educational ecosystem that is more inclusive, flexible, and responsive to the needs of the community. Increased accessibility, parental involvement, student participation, and the development of digital skills serve as evidence that these changes have a significant positive impact.